STUDY OF UTILIZATION FUNCTIONAL FACILITIES OF THE OCEANIC FISHING PORT OF CILACAP CILACAP REGENCY CENTRAL JAVA PROVINCE - Mas Hudi Saputra; Syaifuddin Syaifuddin; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Functional facilities are complementary to basic facilities to facilitate work. Providing services in fishing ports and adding value to all work activities in the port area so that optimal port benefits and uses can be achieved. The purpose of this study was to determine the utilization rate of various functional facilities found in the Cilacap Ocean Fisheries Port. This research was conducted in December 2017 in the Cilacap PPS, Cilacap Regency, Central Java Province, using a descriptive method. The results showed that there were a number of functional facilities in the Cilacap PPS which were still utilized including port offices, workshops and docks, water tanks, electricity networks, gas stations, fish processing, tool and fishing material kiosks, generator houses and beacon lights. While those that are not utilized are fish processing and mini plan. Based on the results of the analysis that has been done, the utilization rate of freshwater tank facilities in Cilacap PPS is 34.6% and the type of utilization is classified as very underutilized. Furthermore, the utilization of the BBM tank facility in the Cilacap PPS is 23.2% of which the type of utilization is classified as not utilized.Keywords: Meskom Village, Gombang, Study of Fishing Ground gombang.